Hollow PUA/PSS/Au microcapsules with interdependent near‐infrared/pH/temperature multiresponsiveness. Issue 7 (23rd October 2015) - Xu, Shuhan; Shi, Jun; Yang, Liu; Wu, Qiong; Cao, Shaokui
ABSTRACT: In this work, smart hollow microcapsules made of thermal‐/pH‐dual sensitive aliphatic poly(urethane‐amine) (PUA), sodium poly(styrenesulfonate) (PSS), and Au nanoparticles (AuNPs) for interdependent multi‐responsive drug delivery have been constructed by layer‐by‐layer (LbL) technique. The electrostatic interactions among PUA, PSS, and AuNPs contribute to the successful self‐assembly of hollow multilayer microcapsules. Thanks to the shrinkage of PUA above its lower critical solution temperature (LCST) and the interaction variation between PUA and PSS at different pH conditions, hollow microcapsules exhibit distinct pH‐ and thermal‐sensitive properties. Moreover, AuNPs aggregates can effectively convert light to heat upon irradiation with near‐infrared (NIR) laser and endow the hollow microcapsules with distinct NIR‐responsiveness. More importantly, the NIR‐responsive study also demonstrates that the microcapsule morphology and the corresponding NIR‐responsive drug release are strongly dependent on the pH value and temperature of the media. The results indicate that the prepared hollow PUA/PSS/Au microcapsules have the great potential to be used as a novel smart drug carrier for the remotely controllable drug delivery. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43008. Abstract :